Kampanye Public Relations #BeautyEverAfter dalam Pengelolaan Limbah Kosmetik: Kecantikan Vs Keberlanjutan - Putri, Ananda Devina; Patrianti, Tria (Prologia, 2023)
Abstract The increase in sales of cosmetic products is directly proportional to the volume of waste that will be generated. Not only packaging waste, chemical waste contained in cosmetics is also harmful to the environment because it contains residues that can reduce the quality of waste when recycled. This research aims to discuss the stages of the Beautynesia #BeautyEverAfter public relations campaign strategy in changing public behavior in managing cosmetic waste and knowing the supporting and inhibiting factors in the #BeautyEverAfter public relations campaign. This research uses Bobbit Sullivan and Anne Gregory's Public Relations Campaign Strategy Theory and Antar Venus' Stages of Behavior Change Theory. The research method used was descriptive qualitative. Data collection was carried out using interview and observation techniques. The results showed that Beautynesia's public relations campaign strategy was successful in one month because it achieved the objectives of the #BeautyEverAfter campaign. In addition, there are supporting and inhibiting factors in the running of the #BeautyEverAfter campaign such as coordination carried out solidly by the Beautynesia team and the team that collaborates the obstacle is that the preparation time for the #BeautyEverAfter campaign is done briefly so that the preparation is not optimal. Abstrak Peningkatan penjualan produk kosmetik berbanding lurus dengan volume limbah yang akan dihasilkan. Tidak hanya sampah kemasan, limbah kimia yang terkandung dalam kosmetik juga berbahaya bagi lingkungan karena mengandung residu sehingga dapat mengurangi kualitas sampah ketika di daur ulang. Penelitian ini bertujuan untuk membahas tahapan strategi kampanye public relations Beautynesia #BeautyEverAfter dalam mengubah perilaku publik mengelola limbah kosmetik dan mengetahui faktor pendukung dan penghambat dalam kampanye public relations #BeautyEverAfter. Penelitian ini menggunakan Teori Strategi Kampanye public relations Bobbit Sullivan dan Anne Gregory serta Teori Tahapan Perubahan Perilaku Antar Venus. Metode penelitian yang digunakan kualitatif deskriptif. Pengumpulan data dilakukan dengan teknik wawancara dan observasi. Hasil penelitian menunjukkan strategi kampanye public relations Beautynesia dikatakan berhasil dalam periode satu bulan untuk mencapai tujuan dari kampanye #BeautyEverAfter. Selain itu, terdapat faktor pendukung dan penghambat dalam berjalannya kampanye #BeautyEverAfter seperti koordinasi dilakukan secara solid oleh tim Beautynesia dan tim yang bekerjasama serta penghambatnya yakni waktu persiapan kampanye #BeautyEverAfter dilakukan secara singkat sehingga persiapan tidak optimal.